PERENCANAAN PERLINDUNGAN DAN PERBAIKAN PANTAI DESA BANYUSANGKA KECAMATAN TANJUNGBUMI KABUPATEN BANGKALAN MADURA - Hari Eko Meiyanto (Media Teknik Sipil, 2012)
A protection and an improvement of shore is essentially if the shorelines setback cause of thesurf hiting and moreever at the beach areas there are settlements or an important buildings. Theplans of the shore protection building is consist of several parameters, including: wind, fetch andwave. The shore protection buildings be able to protect the coast from the blow of the waves andit’s should also be able to withstand the loads around the building. As for the planned the materialprotective buildings are use stone, which is called revetment. The dimensions of the planned revetmentare : a top elevation + 4.00 m, width 1.5 m with two layers of protection and toe protection. Twoprotective layers are the primar layers and secondar layers, the primer thick layers is 1.0 meters andthe secondar thick layers is 0.5 meters, the primar protective stone weight is 0.18 tonnes and 0.018tonnes for secondar.Keyword : The shore protection buildings